Structural, Optical, and Photocatalytic Properties of Sol–Gel-Derived ZnO Nanoparticles for Methylene Blue Degradation - Maria Luruk Seran; Matius Stefanus Batu; Cindy Claudia Christanti; Didi Prasetyo Benu (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2026)
Zinc oxide (ZnO) nanoparticles are attractive photocatalysts due to their wide band gap, chemical stability, and nanoscale-dependent properties. Herein, ZnO nanoparticles were synthesized and systematically characterized to correlate their structural and optical properties with photocatalytic performance. Raman spectroscopy and X-ray diffraction confirmed the formation of a single-phase wurtzite ZnO structure with high crystallinity. UV–Vis diffuse reflectance spectroscopy revealed a distinct absorption edge in the UV region, and the optical band gap was determined to be 3.07 eV using the Kubelka–Munk–Tauc method. The photocatalytic activity of the synthesized ZnO was evaluated via methylene blue degradation under UV irradiation. Time-resolved UV–Vis absorption measurements showed a gradual decrease in the characteristic absorption peak at 660–670 nm, indicating effective dye degradation. A photocatalytic degradation efficiency of 60.55% was achieved after 150 min of irradiation. Kinetic analysis demonstrated that the degradation process followed pseudo-first-order kinetics with an apparent rate constant of 0.0062 min⁻¹. These results demonstrate that the synthesized ZnO nanoparticles exhibit efficient UV-driven photocatalytic activity, highlighting their potential for nanoscale photocatalyst applications. The structure–property–performance correlation established in this work provides insight for further nanostructure and defect engineering strategies to enhance photocatalytic efficiency.